Targeting Pathogenic Postischemic Self-Recognition by Natural IgM to Protect Against Posttransplantation Cardiac Reperfusion Injury. Issue 13 (31st March 2015) - Atkinson, Carl; Qiao, Fei; Yang, Xiaofeng; Zhu, Peng; Reaves, Nicholas; Kulik, Liudmila; Goddard, Martin; Holers, V. Michael; Tomlinson, Stephen
Abstract : Background—: Natural IgM antibodies represent a class of innate pattern recognition receptors that recognize danger-associated molecular patterns expressed on stressed or dying cells. They play important roles in tissue homeostasis by disposing of prenecrotic cells and suppressing inflammation. However, ischemic insult leads to a pathogenic level of IgM binding and complement activation, resulting in inflammation and injury. We investigate the role of self-reactive IgM in the unique setting of transplantation where the donor organ undergoes both cold and warm ischemia and global ischemic insult. Methods and Results—: By transplanting hearts from wild-type donor mice into antibody-deficient mice reconstituted with specific self-reactive IgM monoclonal antibodies, we identified neoepitopes expressed after transplantation and demonstrated a key role for IgM recognition of these epitopes in graft injury. With this information, we developed and characterized a therapeutic strategy that exploited the postischemia recognition system of natural antibodies. On the basis of neoepitope identification, we constructed an anti–annexin IV single-chain antibody (scFv) and an scFv linked to Crry, an inhibitor of C3 activation (scFv-Crry). In an allograft transplantation model in which recipients contain a full natural antibody repertoire, both constructs blocked graft IgM binding and complement activation and significantly reduced graft inflammation and injury. Furthermore, scFv-Crry specifically targeted to the transplanted heart and, unlike complement deficiency, did not affect immunity to infection, an important consideration for immunosuppressed transplant recipients. Conclusions—: We identified pathophysiologically important epitopes expressed within the heart after transplantation and described a novel translatable strategy for targeted complement inhibition that has several advantages over currently available approaches. Abstract : Supplemental Digital Content is available in the text.